Large bowel hernia: pathology and clinic - Croci, Fabio (1984)
Inguinal t,erniai; gf the large bowel constitute a notfrequent variety of hernia, inter¡¡sting fron the patholQ,gical point of view_ ¡md a controversia! su!:>jetct as tQ§urgical tFeatment. E!ased on their per§onal experien,ce, acquireq through the operation of fjfty large bowelsliding hernias the authors analyze the pathogenic1anatomo-pathological, clinic and evolutive